Eye pupil - a window into central autonomic regulation via emotional/cognitive processing - Ferencová, Nikola; Višňovcová, Zuzana; Bona Olexova, Lucia; Tonhajzerová, Ingrid (Physiological research, 2021)
If the eyes are windows into the soul, then the pupils represent at least the gateway to the brain and can provide a unique insight into the human mind from several aspects. The changes in the pupil size primarily mediated by different lighting conditions are controlled by the autonomic nervous system regulated predominantly at the subcortical level. Specifically, parasympathetically-linked pupillary constriction is under the Edinger-Westphal nucleus control and sympathetically-mediated pupillary dilation is regulated from the posterior hypothalamic nuclei. However, the changes in the pupil size can be observed at resting state even under constant lighting, these pupillary changes are mediated by global arousal level as well as by various cognitive factors. In this context, autonomic pathways modulating changes in the pupil size in response to the different light levels can be influenced by multiple central descending inputs driving pupillary changes under steady lighting conditions. Moreover, as the pupillary response is involved in emotional (task-evoked pupillary dilation as an index of emotional arousal) and cognitive (task-evoked pupillary dilation as an index of cognitive workload) stimulation, it can be used to detect the impact of mutual subcortical and cortical structures (i.e. overlapping brain structures included in autonomic, emotional and cognitive regulation) on the pupillary innervation system. Thus, complex understanding of the baseline pupil size ́ and pupillary dynamics ́ mechanisms may provide an important insight into the central nervous system functioning pointing to the pupillometry as a promising tool in the clinical application.
Keywords: autonomní nervový systém; Emotions; Pupil; Humans; Autonomic Nervous System; lidé; Arousal; Cognition; emoce; kognice; arousal; pupila